2023
DOI: 10.1186/s13063-023-07114-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation versus placebo on recovery delay among COVID-19 Tunisian patients: a randomized-controlled clinical trial

Abstract: Introduction The present study aimed to determine the impact of vitamin D supplementation (VDs) on recovery delay among COVID-19 patients. Methods We performed a randomized controlled clinical trial at the national COVID-19 containment center in Monastir (Tunisia), from May to August 2020. Simple randomization was done in a 1:1 allocation ratio. We included patients aged more than 18 years who had confirmed reverse transcription-polymerase chain re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In terms of the efficacy of vitamin D supplementation against COVID-19, aside from the dosage, the repetitiveness of supplementation seems to be a crucial factor in reducing COVID-19-related mortality. In a randomized clinical study carried out in Tunisia, a high, single dose of vitamin D (200,000 IU) did not alter the period of hospitalization in comparison to the placebo group who received physiological saline [44]. However, an observational study conducted in the United Kingdom showed that different regimens of vitamin D3 supplementation, administered during the period of hospitalization, were successful in decreasing mortality among study participants who at the point of hospitalization were vitamin D deficient [45].…”
Section: Discussionmentioning
confidence: 94%
“…In terms of the efficacy of vitamin D supplementation against COVID-19, aside from the dosage, the repetitiveness of supplementation seems to be a crucial factor in reducing COVID-19-related mortality. In a randomized clinical study carried out in Tunisia, a high, single dose of vitamin D (200,000 IU) did not alter the period of hospitalization in comparison to the placebo group who received physiological saline [44]. However, an observational study conducted in the United Kingdom showed that different regimens of vitamin D3 supplementation, administered during the period of hospitalization, were successful in decreasing mortality among study participants who at the point of hospitalization were vitamin D deficient [45].…”
Section: Discussionmentioning
confidence: 94%
“…In total, 17 articles referring to 15 RTCs reported data on vitamin D supplementation in COVID-19 management (Table 2). They were conducted in Tunisia (n = 1 RCT) [44], the United States (n = 2 RCTs) [45,50], Croatia (n = 1 RCT) [46], Russia (n = 2 RCTs) [47,52], Belgium (n = 1 RCT) [49], Spain (n = 1 RCT) [51], Iran (n = 1 RCT) [53], Argentina (n = 1 RCT) [54], India (n = 1 RCT) [58], Mexico (n = 2 RCTs) [59,60], Brazil (n = 1 RCT, n = 3 papers) [55][56][57], and one RCT in four countries [48] (Table 2). The population enrolled was relatively small, ranging from 40 [58] to 240 individuals [55][56][57], with a varying proportion of females, from 37% [48] to 72% [46].…”
Section: Vitamin Dmentioning
confidence: 99%
“…After full article reading, nine articles [16,28,[31][32][33][34][35][36][37] were selected for review and 14 articles were excluded. Reasons for exclusion were: high vs. low dose VDS [38][39][40], no specific numbers of patients who were admitted in ICU [14,15,30,[41][42][43][44][45], failure of randomization [29], and not a randomised trial [46,47]. Characteristics of the nine selected randomised trials are summarized in Table 1.…”
Section: Vds To Covid-19 Patients and Admission To Icumentioning
confidence: 99%